Interpretasi Makna Kalwedo sebagai Salam Persaudaraan di Maluku Barat Daya: Kajian Hermeneutika Gadamer - Misye Waliana; Elka Anakotta (Universitas Palangka Raya, 2026)
Culture and traditions in Southwest Maluku contain a wealth of local wisdom that serves as a social glue, one of which is reflected in the use of the greeting Kalwedo. This greeting is not just a mere pleasantry, but has a very strong meaning in presenting the values ​​of brotherhood and local wisdom of the people of Southwest Maluku. This study shows several things, including, this study aims to interpret the antagonistic meaning of the greeting Kalwedo as a symbol of brotherhood by using the hermeneutic approach of Hans-Georg Gadamer. The research method used is qualitative descriptive-analysis. Data analysis was carried out through three hermeneutic movements, namely phenomenology, reconstruction, and dialogue. The results of the study show that Kalwedo contains the meaning of